Process mechanisms of nanobubble technology enhanced hydrolytic acidification of anaerobic digestion of lignocellulosic biomass - Zhu, Yali; Lyu, Tao; Li, Daoyu; Zhang, Zongqin; Guo, Jianbin; Li, Xin; Xiong, Wei; Dong, Renjie; Wang, Siqi (Elsevier, 2024)
This study explored the efficiency of CO2-, N2-, and H2- nanobubble treatment in anaerobic digestion (AD) of rice straw, with a focus on the processes and metabolic pathways of hydrolytic acidification, and revealed the underlying mechanisms. Mechanistic investigations revealed that nanobubbles, particularly CO2 nanobubbles, significantly increased the degradation of amorphous cellulose, resulting in higher levels of soluble carbohydrates (6.27 % – 11.13 %), VFAs (4.39 % – 24.50 %), and a remarkable cumulative H2 yield (74 – 94 times) Microbial community analysis indicated that the CO2 nanobubble promoted the growth of acidifying bacterial communities, such as Mobilitalea, unclassified_f_Lachnospiraceae, and Bacteroides. This indicates that the introduction of CO2 nanobubbles improved the total abundance of predicted functional enzymes were increased by 14 %, resulting in the production of more easily degradable intermediates. Based on the analysis of total methane production and kinetic analysis, it can be concluded that nanobubble addition enhanced methane production levels of 4.22 %−7.79 % with lower lag time (λ) (0.88–1.06 day) compared to the control group (1.09 day). The results also elucidated changes in relative enzymatic activities involved in the bioconversion of cellulose and hemicellulose during the hydrolysis stage with nanobubble treatment. This work is more beneficial for understanding the promoting effect and mechanism of nanobubbles on AD, facilitating the more precise application of nanobubble technology in the field of renewable energy.
Keywords: bioresources recovery; hydrolytic acidification; micro-nanobubble technology; renewable energy; rice straw; sustainable waste management